Evaluation of dental students’ responses to roleplay videos in a professionalism course - Khalifa S. Al-Khalifa, DrPH; Muhammad A. Nazir, FRSPH (Journal of Taibah University Medical Sciences, 2020)
الملخص: أهداف البحث: تهدف هذه الدراسة إلى تقييم انطباع طلاب طب الأسنان حول مقاطع فيديو تقمص الأدوار في مقرر المهنية التي تم إجراؤها على مدى ثلاث سنوات. طرق البحث: جميع طلاب السنة الثالثة لطب الأسنان (العدد= ٣١٠) الذين شاركوا في مادة المهنية على مدى ثلاث سنوات (٢٠١٦/١٧-٢٠١٨/١٩) تم إشراكهم في هذه الدراسة المقطعية. وتم استخدام هيكل عمل ميلر للكفاءة السريرية مع مقاطع الفيديو التي أنشئها الطلاب، التي تتكون من ١- المعرفة، ٢- الملاحظة، ٣- المحاكاة، ٤- الخبرة. قدم الطلاب في نهاية المقرر، كل عام، إجاباتهم حول مقاطع فيديو تقمص الأدوار باستخدام استبانة تعبأ ذاتيا مكونة من ٢٥ عنصرا. تم تقسيم الاستبانة إلى أربع مجالات/أقسام: ١- إعداد الطالب لإنتاج الفيديو، ٢- المهارات التي طورها إنتاج الفيديو، ٣- فوائد مشاهدة مقاطع الفيديو، ٤- الجوانب العامة للنشاط. النتائج: اتفق معظم الطلاب على أن إنتاج الفيديو وجههم للعمل كفريق (٧٦٪)، فهم التواصل المهني مع الزملاء (٧٠٪) وكذلك المرضى (٦٦٪). وأدرك غالبية الطلبة تحسن مهارات حل المشكلات (٦٧٪) ومهارات إدارة المشاريع (٦٥٪). كما أقر ما يقرب من ثلاثة أرباع الطلبة بفوائد مشاهدة مقاطع الفيديو في تحسين سلوكهم المهني تجاه المرضى. وأظهرت الطالبات وخصوصا الحاصلات على درجات عالية متوسط درجات أكبر لمعظم العناصر (٢٢ و١١ من ٢٥ عنصرا، على التوالي) مع وجود فروق ذات دلالة إحصائية. الاستنتاجات: في هذه الدراسة، كان تأثير مقاطع فيديو تقمص الأدوار ملموسا جدا من قبل غالبية الطلاب. قيمت الطالبات وخصوصا الحاصلات على درجات عالية التعلم بطريقة التدريس هذه تقييما مرتفعا. ويجب أن تكون مهام الفيديو جزءا من مقرر المهنية بطب الأسنان لتحسين مهارات التواصل والسلوك المهني مع الزملاء والمرضى. Abstract: Objective: This study aimed to evaluate dental students’ perceptions of roleplay videos used in a professionalism course that was conducted over three years. Methods: All third-year dental students (N = 310) who participated in a professionalism course over three years (2016/17–2018/19) were included in this cross-sectional study. Miller's framework for clinical competence was used for the student-generated videos, which included 1) knowledge, 2) observation, 3) simulation, and 4) experience. Every year, at the end of the course, the students provided their responses to the roleplay videos using a 25-item self-administered questionnaire. The questionnaire was divided into four sections: 1) student preparations for video production, 2) skills developed through video production, 3) benefits of watching the videos, and 4) general aspects of the activity. Results: Most students agreed that video production led to them working as a team (76%) and understanding professional communication with colleagues (70%) and patients (66%). An improvement in problem-solving skills (67%) and project management skills (65%) was recognised by a majority of the students. Nearly three quarters of the students acknowledged that watching videos improved their professional behaviour towards the patients. Female students and those with high grades showed greater mean scores for most items (22 and 11 out of 25 items, respectively) with significant differences (p < 0.05). Conclusion: In our study, the impact of roleplay videos was recognised by a majority of the students. Female students and those with high grades highly rated learning through this method of teaching. Video assignments should be a part of professionalism courses in dentistry to improve students’ communication skills and professional behaviours with colleagues and patients.